PENGARUH KOMPENSASI, KEPEMIMPINAN, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN - Kustianingsih, Desi Dwi; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to examine the influence of compensation, leadership, and organizational culture to the employee performance. The research objects are the Village Apparatus in the District of Wringinanom which consist of Wringinanom Village, Sumberame Village, Kedunganyar Village, Kepuhklagen Village, Sumberwaru Village, Sembung Village, Kesambenkulon Village, Lebanisuko Village, and Lebaniwaras Village. The samples have been selected by using purposive sampling method. The data collection method has been used by issuing questionnaires. The respondents are 53 respondents. The multiple linear regressions analysis is used as the data analysis. The result of this research shows that the compensation has significant and positive influence to the employee performance. The leadership has significant and positive influence to the employee performance. The organizational culture has significant and positive influence to the employee performance.Keywords: Compensation, Leadership, Organization Culture, Employee Performance.